2021
DOI: 10.1128/spectrum.00755-21
|View full text |Cite
|
Sign up to set email alerts
|

Deubiquitination and Activation of the NLRP3 Inflammasome by UCHL5 in HCV-Infected Cells

Abstract: HCV infection induces inflammation leading to fibrosis, cirrhosis, and cancer. The current study identifies the mechanisms leading to the activation of the NLRP3 inflammasome in hepatocytes, which is an important site of viral replication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Previous studies have highlighted that the ubiquitin/deubiquitination post-translation modification of NLRP3 plays a critical role in regulating the NLRP3 activation. , As a key component of the ubiquitin–proteasome system, the 26S proteasome is responsible for the degradation of various polyubiquitinated proteins in cells, and its inhibition is likely to keep proteins in the polyubiquitination state without being degraded . On the basis of these analyses, we hypothesized that 27 might regulate the ubiquitin-proteasome system to block NLRP3 inflammasome activation via the inhibition of the 26S proteasome.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have highlighted that the ubiquitin/deubiquitination post-translation modification of NLRP3 plays a critical role in regulating the NLRP3 activation. , As a key component of the ubiquitin–proteasome system, the 26S proteasome is responsible for the degradation of various polyubiquitinated proteins in cells, and its inhibition is likely to keep proteins in the polyubiquitination state without being degraded . On the basis of these analyses, we hypothesized that 27 might regulate the ubiquitin-proteasome system to block NLRP3 inflammasome activation via the inhibition of the 26S proteasome.…”
Section: Resultsmentioning
confidence: 99%
“…Uchl5, a deubiquitin enzyme involved in post-translational protein modification, plays a role in oxygen-dependent proline hydroxylation of HIF-α, IL-1 signaling, and neutrophil degranulation ( 47 ). A recent study has demonstrated that Uchl5 can deubiquitinate and activate NLRP3 in HCV-infected cells, leading to IL-1β maturation and secretion ( 48 ). However, its role in NLRP3 caused by cardiac I/R has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…UAF1/USP1 complex activates NLRP3 after deubiquitylation through Lys48 poly-ubiquitin chains and thus increases the level of NLRP3 intracellular levels by protecting it from degradation ( Song et al, 2020 ). UCHL5 deubiquitylation activity has been linked to NLRP3 inflammasome activation in the context of Chronic hepatitis C virus (HCV) infection but the ubiquitin chain types or ubiquitylation sites are unknown ( Ramachandran et al, 2021 ). ABRO1, a subunit of BRISC deubiquitylase complex, binds to NLRP3 in a phosphorylation-dependent manner through Ser194 to mediates the cleavage of Lys63 poly-ubiquitylation of NLRP3 leading to its activation ( Ren et al, 2019 ).…”
Section: Ubiquitylation Of Inflammasome Componentsmentioning
confidence: 99%